A review of the development and current status of wound ostomy continence nurses in the mainland of China - Xiao-li Liu; Ling Wang (Elsevier, 2018)
Wound ostomy continence nurses (WOC nurses), developed as an important part of clinical nurse specialists play an indispensable role in the management of ostomy, all kinds of chronic wounds and incontinent dermatitis. However, there exists a gap compared with developed countries and regions. This paper provides an overview of WOC nurses in China including origin and development, training and accreditation system, roles, values and management, in order to provide references for the development of WOC nurses in China. Keywords: Clinical nurse specialists, Wound ostomy continence, Training, Management